Detection of mandibular canal in human dry mandibles with cone beam computed tomography using 270° and 360° protocols under continuous and pulse modes - A comparative study - Karishma; A G Annaji; N Rakesh; L Upasana; M S Abhinetra (Wolters Kluwer Medknow Publications, 2021)
Background: Cone beam computed tomography (CBCT) enables practitioner to accurately localize and mark the nerve canal. The rotation of the X-ray tube and the detector around the patient's head produces multiple projection images. A high number of projections is associated with increased radiation dose to the patient, higher spatial and contrast resolution. Shorter scan arc results in reduced scan time, reduced dose and smaller file sizes. The pulsed X-ray beam reduces the actual exposure time than the scanning time and the patient radiation exposure. Aim: (1) To assess and compare the diagnostic efficacy between pulse mode and continuous mode (2) To assess and compare the diagnostic efficacy between 270° and 360° CBCT rotational protocols Subjects and Methods: A total of 30 Intact Dentate or Partially dentate dry human mandibles consisting first, second, and third molars were subjected to a total of 4 CBCT scans: 270° rotation scans under continuous and pulse mode, 360° rotation scans under continuous and pulse mode using two CBCT units. Distance from the inferior cortical border of mandible (ICBM) to the roof of the inferior alveolar nerve canal (IANC) was measured at four locations: mental foramen, first, second and third molar. The results were then compared. Results: Comparison of the IANC length measurements for the two modes revealed no significant difference. Conclusion: Shorter scan arc and pulse mode can be adopted in patients finding it difficult to remain stable for prolonged periods of time, while maintaining appreciable clarity and quality of image. This could apply to geriatric patients, children, mentally challenged, in patients with trauma, neurological diseases, anxiety, claustrophobia, wherein the patient's movements might need re-scanning, which would lead to an extra radiation dose to the patient.